Addition of molybdenum into amorphous glass‐coated microwires usable as temperature sensors in biomedical applications. Issue 2 (18th November 2015) - Hudak, Radovan; Varga, Rastislav; Polacek, Irenej; Klein, Peter; Skorvanek, Ivan; Komanicky, Vladimir; del. Real, Rafael P.; Vazquez, Manuel
Abstract : Compared to other sensors, such as radio‐frequency identification sensors, microwires have a significant advantage due to their small dimensions and contact‐free reading. The most important advantage is that a microwire is considered to be a biocompatible material due to the glass‐coating insulator. This is particularly applicable in various titanium implants (dental, knee joint, replacement of damaged skull part, repair of the femur, etc.). The temperature dependence of the switching field can be employed to monitor inflammatory processes. In this contribution we present the influence of molybdenum (Mo) content on the magnetic properties and thermal treatment in order to obtain a strong variation of the switching field to temperature. We show that stress annealing of a FeMo9 BCu microwire at 775 K under an applied axial stress of 309 MPa leads to the strongest variation in a temperature range from 300 to 315 K, which is highly desirable for biomedical applications.